Experimental Study on the Progressive Collapse Resistance of Two-Storey Half-Scale Fabricated Reinforced Concrete Column-Steel Beam Composite Frame Structure - Youquan Liu; Jingang Xiong; Jiancong Wen (Advances in Civil Engineering)
Progressive collapse behavior of case-in-place concrete and steel frame structures has been extensively investigated over the past years. However, studies on progressive collapse resistance and characteristics of prefabricated RCS composite frame structure (space frame) are limited. In this study, a half-scale prefabricated RCS space frame structure (two-storey, 1 × 2-bay) was designed and manufactured and then tested through the sudden failure of the long-side central column. The weakened part of failure column was rapidly pulled out using vehicle traction force, and displacement was obtained with a dynamic data acquisition instrument supplemented by high-speed camera to record the deformation process of the structure. Additionally, the remaining structure displacement variation and the beam-to-column connections of fem model under progressive collapse were simulated using SAP2000. The FEA results were compared with the experimental results to verify the effectiveness of the numerical analysis. Experimental results demonstrated that the prefabricated RCS composite frame structure designed in accordance with Chinese building codes shows improved resistance to progressive collapse. The dynamic effect demonstrates no significant influence on the prefabricated RCS composite frame structure, and the suggested dynamic amplification coefficient is 1.28. Steel plates (A, B, and C) of the beam-to-column connection are the weak part of the structural failure, and appropriate measures should be applied to strengthen the steel plate of the beam-to-column connection when the prefabricated RCS composite frame structure is designed to resist progressive collapse. SAP2000 FEM program verified that the numerical simulation results are basically consistent with the experimental results.